On two geometric inequalities - Simon, Alice; Volkmann, Peter (Annales Mathematicae Silesianae, 1995)
In inner product spaces the Ptolemaic inequality (1) and the quadrilateral inequality (2) are well known. By using the identity (3), we derive here (2) from (1). The rest of the paper is devoted to some comments on (1), (2), (3).